Features of the Eye Hydrodynamics on the Background of Thyroid Dysfunctions - V. G. Likhvantseva; E. V. Korosteleva; T. E. Borisenko; M. M. Skopintseva (Oftalʹmologiâ, 2020)
Purpose: to study the features of eye hydrodynamics in patients with thyroid dysfunctions.Patients and methods. The material for this study was the results of a survey of 43 patients (86 eyes) with thyroid dysfunctions: 23 people (46 eyes) with primary untreated hypothyroidism (PGT) and 20 people (40 eyes) with primary untreated thyrotoxicosis (PTT). There weren’t ophthalmic hypertension and glaucoma There weren’t signs of ophthalmic hypertension and glaucoma in the patients included in this study at the stage of primary ophthalmologic diagnostics.Results. Correlation analysis revealed a causal relationship between the ratio of T4 / TSH hormones, on the one hand, and indicators of secretion of aqueous humor per unit of time and ease of outflow, on the other hand. In the group of patients with hypothyroidism, a weak linear inverse correlation was found between the ratio of free thyroxine and thyroid stimulating hormone and the minute volume of aqueous humor: according to the regression model, an increase in the ratio of T4 / TSH hormones by 1 was accompanied by a decrease in the minute volume of aqueous humor by 3 units. In patients with thyrotoxicosis, a statistically significant inverse linear correlation was found between the ratio of the T4 / TSH hormones and the coefficient of ease of outflow. According to the regression model, with an increase in the ratio of hormones T4 / TSH by 1, the coefficient of lightness of outflow decreases by 5 units. The presence of thyroid receptors in the cytoplasm and nuclei of the endothelium cells of the trabecular apparatus, the nuclei of fibroblasts forming the stroma of the trabeculae, as well as in the nuclei of the pigment and non-pigment epithelium of the processes of the ciliary body substantiates the molecular basis of the causal connection of thyroid dysfunctions with hydrodynamic disorders The conducted studies confirm the modern concept that the control of regulation of the tissue and organ homeostasis is carried out by the coordinated interaction of 3 systems: nervous, endocrine, and immune. Regression modeling clearly shows a pronounced causal relationship between thyroid dysfunctions and hydrodynamic processes in the eye.Conclusion. The results of clinical studies demonstrate the fact of controlling regulation by hydrodynamic processes at the eye level by the endocrine system, explain the possible mechanism on a morphological basis, and reveal the potential of a new therapeutic strategy.